Media transformation management strategy in the era of multiplatform (Case study on Tribun network) - Tripalupi, Merry Fridha; Irawan, Rahmat Edi (Jurnal Komunikasi, 2025)
The rapid advancement of technology demands that media companies transform quickly; it is insufficient for media to produce content; they must adopt an integrated multi-platform strategy. This study examines media transformation management strategies in the multi-platform era, utilizing the Tribun Network as a case study. The research employs a descriptive qualitative method with a case study approach. This study utilizes Henry Jenkins' theory of media convergence and a cross-media approach to analyze channel integration and content distribution patterns. The results indicate that Tribun's transformation encompasses digital editorial integration, leadership restructuring towards a flexible model, platform-based content optimization, and diversification of monetization channels. This strategy has not only expanded audience reach but has also established an editorial workflow that is responsive to algorithms and technological dynamics. This research contributes to the literature on digital media management and is a practical reference for other media organizations in designing multi-platform strategies.